EFFECTS OF TRANSPARENCY-FOCUSED SOCIAL ACCOUNTABILITY ACTIONS ON PUBLIC SERVICE DELIVERY IN KAKAMEGA COUNTY GOVERNMENT MINISTRIES, KENYA - Barasa, Patrick Simiyu; Shitetswa, Ayub; Ngome, Charles Kibanani (IJRDO - Journal of Business Management, 2023)
The provision of public services in the Republic of Kenya has encountered difficulties over the years. The implementation of many policies, such as performance contracts and measurement and evaluation, has not produced the desired outcomes. Therefore, it was necessary to concentrate on alternative approaches to enhance public service delivery, such as the implementation of social accountability measures. By encouraging openness through social accountability initiatives, corruption and bureaucratic inefficiencies are reduced, which enhances the delivery of services. Few studies have examined the link between the acts of social of accountability and delivery of services in Kenya, despite the fact that they are, thought to increase service delivery in the public sector. This study therefore sought to interrogate the effect of transparency-focused social accountability actions on public service delivery in Kakamega County Government Ministries, Kenya. The study was centered on Vance, Lowry, and Eggett's Accountability theory (2015). The research used a descriptive survey research approach. The employees from different ministries, county assembly members, as well as chief officers, who take part in public decision-making processes, made up the target population. A population of 1,904 persons was targeted. Accordingly, using Krejcie and Morgan (1970) table, a sample size of 322 was obtained. To analyse the quantitative data, the researcher employed the Statistical Package for Social Sciences. Content analysis was, used to look at qualitative data. The research instruments’ validity was certified by the experts in the area of study, while reliability of the research instruments was determined by use of Cronbach's alpha coefficient. This was meant to check on the internal consistency of the research instruments. A standardized questionnaire and interviews was used to collect the data, which was then analyzed using descriptive and inferential statistics and presented using tables. For this investigation, a multivariate regression analysis was, used. The findings revealed that transparency focused (β=.652, p<.05) had a positive significant effect on service delivery and accounted for 41.7%. The employees of Kakamega County may gain from this research because it will allow them to engage in more discussions with the county by engaging in advisory boards, project implementation, and project feasibility analysis, all of which can enhance the county's provision of public services.